NOWELIZACJA KODEKSOWEJ REGULACJI UMOWY UBEZPIECZENIA - ZAGADNIENIA DE LEGE FERENDA - Kowalewski, Eugeniusz (Zeszyty Prawnicze, 2017)
Insurance Contract in the Civil Code after the Amendment Summary After many years of work on an extensive reform of the economic Insurance law on 22 May 2003 four new acts were passed. O ne of the aims of the reform was to set in order provisions applying to an Insurance contract, which so far had been regulated not only in the Civil Code (art. 805-834), but also in the Act of 28 July 1990 about an insurance activity (art. 6-8). A new Insurance Activity Act which came into force on l January 2004 in principle does not include legal norms applying to the insurance contract. These norms - with necessary modifications - have been transferred into the Civil Code. Subject to art. 233 of the Act relevant modifications have been introduced to art. 807 § 2, art. 812 § 1-8, art. 817 § 2 and art. 822 § 1-4. Moreover, two new regulations have been implemented, namely art. 824 § 1-2 and art. 384 § 5. The above-mentioned changes are of great importance and can be called „a small amendment of the insurance contract in the Civil Code”. The author makes an argument that the recent changes of the insurance contract are far insufficient from the point o f view of a modern insurance business.